HLA‐dependent variation in SARS‐CoV‐2 CD8 + T cell cross‐reactivity with human coronaviruses. Issue 1 (7th March 2022) - Buckley, Paul R.; Lee, Chloe H.; Pereira Pinho, Mariana; Ottakandathil Babu, Rosana; Woo, Jeongmin; Antanaviciute, Agne; Simmons, Alison; Ogg, Graham; Koohy, Hashem
Abstract: The conditions and extent of cross‐protective immunity between severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) and common‐cold human coronaviruses (HCoVs) remain open despite several reports of pre‐existing T cell immunity to SARS‐CoV‐2 in individuals without prior exposure. Using a pool of functionally evaluated SARS‐CoV‐2 peptides, we report a map of 126 immunogenic peptides with high similarity to 285 MHC‐presented peptides from at least one HCoV. Employing this map of SARS‐CoV‐2‐non‐homologous and homologous immunogenic peptides, we observe several immunogenic peptides with high similarity to human proteins, some of which have been reported to have elevated expression in severe COVID‐19 patients. After combining our map with SARS‐CoV‐2‐specific TCR repertoire data from COVID‐19 patients and healthy controls, we show that public repertoires for the majority of convalescent patients are dominated by TCRs cognate to non‐homologous SARS‐CoV‐2 peptides. We find that for a subset of patients, >50% of their public SARS‐CoV‐2‐specific repertoires consist of TCRs cognate to homologous SARS‐CoV‐2‐HCoV peptides. Further analysis suggests that this skewed distribution of TCRs cognate to homologous or non‐homologous peptides in COVID‐19 patients is likely to be HLA‐dependent. Finally, we provide 10 SARS‐CoV‐2 peptides with known cognate TCRs that are conserved across multiple coronaviruses and are predicted to be recognized by a high proportion of the global population. These findings may have important implications for COVID‐19 heterogeneity, vaccine‐induced immune responses, and robustness of immunity to SARS‐CoV‐2 and its variants. Abstract : We identified 126 SARS‐CoV‐2 T cell targets that exhibit cross‐reactive potential with HCoV predicted peptide‐MHC. We found a subset of COVID‐19 patients whose SARS‐CoV‐2‐specific public TCRs are primarily directed toward these targets with cross‐reactive potential. For these patients, we found distinct HLA profiles. It is plausible that such patients may exhibit more robust protection against SARS‐CoV‐2 and its variants. Ten of the identified SARS‐CoV‐2‐HCoV peptides are highly conserved across multiple coronaviruses and are predicted to invoke T cell responses in high proportions of the global population, which is an encouraging insight in the search for pan‐coronavirus T cell targets.